Proteomic Changes of Osteoclast Differentiation in Rheumatoid and Psoriatic Arthritis Reveal Functional Differences - Kovács, Orsolya Tünde; Tóth, Eszter; Ozohanics, Olivér; Soltész-Katona, Eszter; Marton, Nikolett; Buzás, Edit Irén; Hunyady, László; Drahos, László; Turu, Gábor; Nagy, György (Frontiers in Immunology, 2022)
Background: Osteoclasts play a crucial role in the maintenance, repair, and remodeling of bones of the adult vertebral skeleton due to their bone resorption capability. Rheumatoid arthritis (RA) and psoriatic arthritis (PsA) are associated with increased activity of osteoclasts. Objectives: Our study aimed to investigate the dynamic proteomic changes during osteoclast differentiation in healthy donors, in RA, and PsA. Methods: Blood samples of healthy donors, RA, and PsA patients were collected, monocytes were isolated and differentiated into osteoclasts in vitro using M-CSF and RANK-L. Mass spectrometry-based proteomics was used to analyze proteins from cell lysates. The expression changes were analyzed with Gene Set Enrichment Analysis (GSEA). Results: The analysis of the proteomic changes revealed that during the differentiation of the human osteoclasts, expression of the proteins involved in metabolic activity, secretory function, and cell polarity is increased; by contrast, signaling pathways involved in the immune functions are downregulated. Interestingly, the differences between cells of healthy donors and RA/PsA patients are most pronounced after the final steps of differentiation to osteoclasts. In addition, both in RA and PsA the differentiation is characterized by decreased metabolic activity, associated with various immune pathway activities; furthermore by accelerated cytokine production in RA. Conclusions: Our results shed light on the characteristic proteomic changes during human osteoclast differentiation and expression differences in RA and PsA, which reveal important pathophysiological insights in both diseases.